Predictors of willingness to eat wild mushrooms: extended theory of reasoned action - Gong, Fangmin; Zhuang, Jingwen; Liu, Han; Li, Zhenyi; Jia, Yuhan; Du, Juan; Huang, Xincheng; Chen, Si (Frontiers in Nutrition, 2025)
BackgroundThe accidental consumption of wild poisonous mushrooms has emerged as a primary source of poisoning incidents globally. It is imperative to comprehend the dietary habits of individuals consuming wild mushrooms to address this issue effectively.MethodsIn this investigation, an extended version of the theory of reasoned action was employed, incorporating perceived benefit and food-related self-efficacy as novel predictive variables.ResultsA total of 793 Chinese residents participated in the study, which revealed that subjective norms (β = 0. 219, t = 5.314), attitudes (β = 0.426, t = 8.237), self-efficacy (β = 0.144, t = 5.905), and perceived benefit (β = 0.177, t = 4.586) significantly influenced the participants' intentions.ConclusionThe extended theory of reasoned action framework has proven to be a valuable instrument for understanding individuals' inclinations toward selecting food-related risks. These factors should be considered in governmental initiatives aimed at enhancing food safety.